Aid for development : the key issues (Washington, D.C. : Joint Ministerial Committee of the Boards of Governors of the World Bank and the International Monetary Fund on the Transfer of Real Resources to Developing Countries (Developing Committee), 1986)
This is the final report of the Task Force on concessional flows with topics ranging from: what are concessional flows, reasons for aid, need for aid, distribution and use of aid, performance of recipients, effectiveness of aid among others.
Supporting materials for the report of the task force on concessional flows.
lje 20/04/2018
Loans
Keywords: Economic assistance